A Tanizaki Feast The International Symposium in Venice - Boscaro, Adriana; Hood Chambers, Anthony (Michigan Monograph Series in Japanese Studies, 2020)
This volume presents 18 eighteen essays, written by scholars from six countries, on Tanizaki Jun'ichiro (1886-1965), one of the great writers of the 20th century. The essays were originally prepared for a landmark international symposium in Venice in 1995, at which 22 speakers addressed an audience of about two hundred students and scholars in the Aula Magna of the University of Venice. Topics include Tanizaki's fiction, plays, and film scenarios; his aesthetics; his place in Japanese intellectual history; his depiction of the West; his use of humor; and film adaptations of his works. In 1964 Tanizaki was elected to honorary membership in the American Academy and Institute of Arts and Letters, the first Japanese to be so honored; and it is widely believed that he was being considered for the Nobel Prize in Literature.